Evaluasi Resiliensi Pasien Penyalahguna Narkotika Di Balai Besar Rehabilitasi Badan Narkotika Nasional - Dipa Tri Adhitya; Palupi Lindiasari Samputra (Universitas Batanghari Jambi, 2021)
BNN RI Regulation Number 24 of 2017 concerning Rehabilitation Services for Addicts and Victims of Narcotics Abuse has the authority to carry out rehabilitation for narcotics users. Rehabilitation helps the addict recover from his addiction to drugs. With good resilience, the patient will be able to recover or adjust to adversity. This study aimed to analyze the factors that determine the level of strength and analyze the resilience index of narcotic abusers undergoing rehabilitation at the BNN Rehabilitation Center. This study used a quantitative method of survey type with a sample of 140 respondents. The data analysis method used factor analysis and index of resilience level. The results showed five factors of the resilience of addicts, namely Impulse Control, Empathy, Emotion Regulation, Achievement, and Problem Analysis. These five factors can explain the effect on the strength of 63.079%. Addicts show a high level of resilience of 82.33% after following a rehabilitation program